2007
DOI: 10.1063/1.2711536
|View full text |Cite
|
Sign up to set email alerts
|

Dominant effect of near-interface native point defects on ZnO Schottky barriers

Abstract: The authors used depth-resolved cathodoluminescence spectroscopy and current-voltage measurements to probe metal-ZnO diodes as a function of native defect concentration, oxygen plasma processing, and metallization. The results show that resident native defects in ZnO single crystals and native defects created by the metallization process dominate metal-ZnO Schottky barrier heights and ideality factors. Results for ZnO(0001¯) faces processed with room temperature remote oxygen plasmas to remove surface adsorbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
105
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(115 citation statements)
references
References 24 publications
(18 reference statements)
9
105
0
Order By: Relevance
“…All values fall comfortably within the range of ZnO Schottky-barrier heights reported by others ͑0.6-1.0 eV͒. [7][8][9][10][11]17,18 Another measure of the rectifying quality is the ideality factor ͑n͒, with a value of 1 corresponding to a perfect exponential transition from leakage-current to forward-current flow. High values of the ideality factor ͑Ͼ2͒ are attributed to the existence of multiple current pathways.…”
mentioning
confidence: 91%
“…All values fall comfortably within the range of ZnO Schottky-barrier heights reported by others ͑0.6-1.0 eV͒. [7][8][9][10][11]17,18 Another measure of the rectifying quality is the ideality factor ͑n͒, with a value of 1 corresponding to a perfect exponential transition from leakage-current to forward-current flow. High values of the ideality factor ͑Ͼ2͒ are attributed to the existence of multiple current pathways.…”
mentioning
confidence: 91%
“…8 Previous ZnO surface studies revealed the importance of surface adsorbates, near-interface native defects, and thermally induced interface chemical interactions at metal/ZnO contacts. 3,9,10 Stabilization mechanisms of Zn͑0001͒-or O͑0001͒-terminated faces are still controversial, yet few experimental studies compare them. 11 Differences between hydrothermal ZnO polar surfaces were ascribed to surface band bending induced by spontaneous polarization, 12 while melt-grown ZnO exhibits only a small difference in band bending.…”
mentioning
confidence: 99%
“…For example, resident and metallization-induced native defects were reported to severely degrade the potential barrier height and ideality factor of metal-ZnO Schottky diodes, acting as a conducting path for charge carriers. 7 For optical applications of ZnO, DLs responsible for so-called green luminescence ͑GL͒ have been one of the obstacles for realizing ZnO light emitters. Furthermore, the nature of GL remained controversial for decades.…”
mentioning
confidence: 99%